Rekonstruksi Kebijakan Ekonomi Rasulullah pada masa Modern: Pendekatan Riil, Moneter, dan Fiskal - Annisa Maulidia Alfian; Rozalinda; Meirison; Alfian (Universitas Muhammadiyah Jember, 2025)
This article aims to reconstruct Islamic economic policy based on the practice of the Prophet Muhammad with an integrated approach between the real, monetary and fiscal sectors. By using a qualitative literature study method through historical and normative analysis, this research examines how the Prophet built an economic system that is fair, sustainable, and in accordance with maqashid al-shariah. In the real sector, the Prophet created the Madinah market as an economic space free from monopoly, hoarding, and fraudulent practices, and upheld business ethics. In the monetary sector, the prohibition of usury and the use of intrinsic value-based currencies demonstrate a commitment to value stability and fairness in transactions. While in the fiscal sector, the management of zakat, jizyah, and baitul mal reflect redistributive policies that encourage social welfare and economic empowerment of the people. The findings recommend that contemporary economic policies, especially in Muslim countries, consider the integration of these three sectors as a unit that encourages an inclusive and benefit-based Islamic economic system. The practical implications include the importance of market reforms, transformation of productive Islamic financing systems, and strengthening the role of Islamic fiscal in the public policy framework.